Blunt impact - Black, Lisa, 1963- (Black, Lisa, 1963- Theresa MacLean novels., 2012)
Forensic scientist Theresa MacLean is puzzled by the questionable death of a female construction worker at a Cleveland building site. A witness to the death - a young girl nicknamed Ghost - may be able to help. Ghost says the woman was pushed by someone she can only identify as the Shadow Man. Soon Theresa finds herself in a race against time to protect Ghost from an unknown killer before he is able to find the little girl and silence her for good.